Clinical and functional differences between early-onset and late-onset adult asthma: a population-based Tasmanian Longitudinal Health Study. Issue 11 (14th June 2016) - Tan, Daniel J; Walters, E Haydn; Perret, Jennifer L; Burgess, John A; Johns, David P; Lowe, Adrian J; Lodge, Caroline J; Hayati Rezvan, Panteha; Simpson, Julie A; Morrison, Stephen; Thompson, Bruce R; Thomas, Paul S; et al.
Abstract : Background: Differences between early-onset and late-onset adult asthma have not been comprehensively described using prospective data. Aims: To characterise the differences between early-onset and late-onset asthma in a longitudinal cohort study. Methods: The Tasmanian Longitudinal Health Study (TAHS) is a population-based cohort. Respiratory histories and spirometry were first performed in 1968 when participants were aged 7 (n=8583). The cohort was traced and resurveyed from 2002 to 2005 (n=5729 responses) and a sample, enriched for asthma and bronchitis participated in a clinical study when aged 44 (n=1389). Results: Of the entire TAHS cohort, 7.7% (95% CI 6.6% to 9.0%) had early-onset and 7.8% (95% CI 6.4% to 9.4%) late-onset asthma. Atopy and family history were more common in early-onset asthma while female gender, current smoking and low socioeconomic status were more common in late-onset asthma. The impact on lung function of early-onset asthma was significantly greater than for late-onset asthma (mean difference prebronchodilator (BD) FEV1 /FVC −2.8% predicted (−5.3 to −0.3); post-BD FEV1 FVC −2.6% predicted (−5.0 to −0.1)). However, asthma severity and asthma score did not significantly differ between groups. An interaction between asthma and smoking was identified and found to be associated with greater fixed airflow obstruction in adults with late-onset asthma. This interaction was not evident in adults with early-onset disease. Conclusions: Early-onset and late-onset adult asthma are equally prevalent in the middle-aged population. Major phenotypic differences occur with asthma age-of-onset; while both share similar clinical manifestations, the impact on adult lung function of early-onset asthma is greater than for late-onset asthma.